Genomic Analysis of an Indian G8P[1] Caprine Rotavirus-A Strain Revealing Artiodactyl and DS-1-Like Human Multispecies Reassortment - Sircar, Shubhankar; Malik, Yashpal Singh; Kumar, Prashant; Ansari, Mohd Ikram; Bhat, Sudipta; Shanmuganathan, S.; Kattoor, Jobin Jose; Vinodhkumar, O.R.; Rishi, Narayan; Touil, Nadia; Ghosh, Souvik; Bányai, Krisztián; et al. (Frontiers in Veterinary Science, 2021)
The surveillance studies for the presence of caprine rotavirus A (RVA) are limited in India, and the data for the whole-genome analysis of the caprine RVA is not available. This study describes the whole-genome-based analysis of a caprine rotavirus A strain, RVA/Goat-wt/IND/K-98/2015, from a goat kid in India. The genomic analysis revealed that the caprine RVA strain K-98, possess artiodactyle-like and DS-1 human-like genome constellation G8P[1]-I2-R2-C2-M2-A3-N2-T6-E2-H3. The three structural genes (VP2, VP4 and VP7) were close to caprine host having nucleotide-based identity range between 97.5 to 98.9%. Apart from them, other gene segments showed similarity with either bovine or human like genes, ultimately pointing towards a common evolutionary origin having an artiodactyl-type backbone of strain K-98. Phylogenetically, the various genes of the current study isolate also clustered inside clades comprising Human-Bovine-Caprine isolates from worldwide. The current findings add to the knowledge on caprine rotaviruses and might play a substantial role in designing future vaccines or different alternative strategies combating such infections having public health significance. To the best of our knowledge, this is the first report on the whole-genome characterization of a caprine RVA G8P[1] strain from India. Concerning the complex nature of the K-98 genome, whole-genome analyses of more numbers of RVA strains from different parts of the country are needed to comprehend the genomic nature and genetic diversity among caprine RVA.